Access to sustainable electrification: Possibilities for rural Mozambique. Issue 1 (1st January 2020) - Uamusse, Miguel M.; Tussupova, Kamshat; Persson, Kenneth M.; Bengtsson, Lars; Berndtsson, Ronny
Abstract: We assess the sustainability of rural electrification in Manica Province, Mozambique, focusing on different alternatives for mini-grid and off-grid power supply. The qualitative assessment considers four dimensions of sustainability, namely environmental, socio-cultural, economic, and institutional. We argue that small-scale hydropower is the most sustainable alternative for off-grid or mini-grid solutions in rural Manica Province with good possibilities to scale up this to the major parts of rural Mozambique. The investigation shows that social acceptance for small-scale hydropower is high. Environmental sustainability of small-scale hydropower is higher than for PV systems. To speed up the electrification process, efficient rural electrification has to connect policy to local scale and institutional strengthening. The legislation needs to be improved, and there is a need for better institutional coordination for hydropower mini-grids' regulation. Along this line, a national framework to support small and independent power producers is necessary.